2005
DOI: 10.1080/10884600500328155
|View full text |Cite
|
Sign up to set email alerts
|

CE FEATURE Alternative Diversion Programs for Nurses with Impaired Practice: Completers and Non-Completers

Abstract: The purpose of this study was to describe, explain, and compare the experiences of nurses who were completers and non-completers of an alternative diversion program for chemically dependent nurses. Risk factors for substance abuse are explored.Sixteen nurses who had participated in an alternative diversion program for chemically dependent nurses were interviewed for this study. Fourteen of these nurses completed second interviews. Qualitative analysis of these interviews was conducted utilizing the constant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 44 publications
(37 reference statements)
0
27
0
Order By: Relevance
“…nurses' easy access to drugs, a structural factor situated in nurses' physical work environments, is commonly posed as a chief contributor toward their use of substances (Darbro, ; Dittman, ; Kenna & Wood, ; Lillibridge et al., ; Trinkoff, Storr, & Wall, ). To support this contention, researchers have frequently cited data showing that the level of nurses' workplace access to drugs correlates with their prevalence of abusing the accessible drugs therein (Bozimowski, Groh, Rouen, & Dosch, ; Bugle, ; Trinkoff & Storr, ; Trinkoff et al., ).…”
Section: Contributory Factors Of Access Stress and Attitudementioning
confidence: 99%
See 1 more Smart Citation
“…nurses' easy access to drugs, a structural factor situated in nurses' physical work environments, is commonly posed as a chief contributor toward their use of substances (Darbro, ; Dittman, ; Kenna & Wood, ; Lillibridge et al., ; Trinkoff, Storr, & Wall, ). To support this contention, researchers have frequently cited data showing that the level of nurses' workplace access to drugs correlates with their prevalence of abusing the accessible drugs therein (Bozimowski, Groh, Rouen, & Dosch, ; Bugle, ; Trinkoff & Storr, ; Trinkoff et al., ).…”
Section: Contributory Factors Of Access Stress and Attitudementioning
confidence: 99%
“…In our preliminary readings of the works on predisposing factors, however, we found that the literature was almost exclusively centered on the identification and measurement of individual risk factors. These included the following: use of substances, particularly benzodiazepines or opioids prior to entering nursing (Mynatt, ; Rojas, Jeon‐Slaughter, Brand, & Koos, ); comorbid medical (Sullivan, ) or psychiatric (Breslin, ; Darbro, ; Rojas et al., ) illnesses; history of childhood abuse or sexual trauma (Breslin, ; Dittman, ; Strom‐Paikin, ; Sullivan, ,b); socializing with others who abuse substances (Kenna & Lewis, ); absence of proscriptions against substance use (Beamer, ; Trinkoff, Zhou, Storr, & Soeken, ); ‘sensation‐ or thrill‐seeking’ personality (Trinkoff & Storr, ; West, ); family history of addictions (Bugle, ; Kenna & Lewis, ; Kenna & Wood, , ; Stammer, ); use of substances to self‐medicate emotional distress or physical pain (Darbro, ; Dittman, ; Hutchinson, , ; Lillibridge, Cox, & Cross, ; Stammer, ); and male gender (Bugle, ; McNelis et al., ). Multifactorial explanations involving any combination of these individual risk factors have also been offered (West, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Third, it would appear that alternative programs are more effective in moving quickly to protect the public from unsafe practitioners than are disciplinary programs, since such nurses are removed from the healthcare setting swiftly through early identification and begin treatment within a few weeks, compared to the months or even years before the final adjudication of nurses in disciplinary programs (Sullivan et al 1990;Quinlan 2003). Fourth, those who have successfully completed an alternative program are highly motivated to retain their license, feel an affinity with other recovering nurses, and have a plan to prevent relapse (Darbro 2005). Programs vary from state to state but they are selective about eligibility in order to protect the public.…”
Section: The Traditional Disciplinary Approach Vs Alternative Approamentioning
confidence: 95%
“…In particular, they cited being more patient, tolerant and compassionate. Furthermore the monitoring experience helped nurses recognize the need to utilize more social support [28].…”
Section: Discussionmentioning
confidence: 99%